2009
DOI: 10.1136/pgmj.2008.076307
|View full text |Cite
|
Sign up to set email alerts
|

A review of novel biological tools used in screening for the early detection of lung cancer

Abstract: Lung cancer is the most common cancer worldwide and causes more deaths per year than any other cancer. It has a very poor 5-year survival rate of 8-16%, partly because of comorbidity preventing curative treatments but mainly because of the disease presenting with symptoms only when it is at an advanced and incurable stage. When lung cancer is detected earlier and is amenable to radical treatments such as potentially curative surgery and radical radiotherapy, 5-year survival rates are much higher (up to 67%). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 41 publications
1
44
0
1
Order By: Relevance
“…One recent review states: "Overall, no single cheap and reliable test has yet been identified for the effective screening of lung cancer in large population studies, but work is in progress." 5 Effective and financially feasible screening for patients at a high risk of developing lung cancer is, therefore, a high research priority.…”
mentioning
confidence: 99%
“…One recent review states: "Overall, no single cheap and reliable test has yet been identified for the effective screening of lung cancer in large population studies, but work is in progress." 5 Effective and financially feasible screening for patients at a high risk of developing lung cancer is, therefore, a high research priority.…”
mentioning
confidence: 99%
“…Biological tools, such as testing serum for tumour-associated antibodies, detection of gene-promoter hypermethylation in sputum samples, exhaled breath volatile organic compounds and detection of novel proteins in serum or sputum are also in development 31 . Unfortunately, none of these is currently ready for use in clinical practice.…”
Section: Screeningmentioning
confidence: 99%
“…It can be categorized into two sub-types: nonsmall cell lung cancer (Koh et al, 2012) and small cell lung cancer. Despite many efforts to improve lung cancer outcome, long-term survival has not improved significantly over the last 20 years, with a 5-year cumulative survival rate that remains very dismal at only 15% (Ghosal et al, 2009). Current standard therapies limited to chemotherapy and radiotherapy or both rarely cure this disease, thus accentuating the need for more effective and alternate therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%